High-wear-resistance anti-fatigue ultra-high molecular weight polyethylene rope and preparation method thereof

By using the synergistic effect of modified silicon carbide and other materials in ultra-high molecular weight polyethylene cables, the hardness and wear resistance of fiber fibrous wires are improved, the wear problem of moored cables is solved, and the service life is extended.

CN119121665APending Publication Date: 2024-12-13YANGZHOU XINGLUN ROPE CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411281538.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene cables are easily worn due to friction when used as mooring cables, which affects their service life.

Method used

Using fiber fibrous filaments braided from ultra-high molecular weight polyethylene resin, bauxite, anti-wear powder, lubricant and one-dimensional filler material, improve the hardness and resistance of the cable through the synergy between modified silicon carbide and other materials. Abrasive performance, reduce friction and wear.

Benefits of technology

It significantly extends the service life of the cable, can more effectively withstand friction when in contact with objects such as ships, cable piles, etc., and has long wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041774210000071
    Figure BDA0005041774210000071
  • Figure BDA0005041774210000072
    Figure BDA0005041774210000072
  • Figure BDA0005041774210000073
    Figure BDA0005041774210000073
Patent Text Reader

Abstract

The invention relates to the technical field of ropes, and particularly discloses a high-wear-resistance anti-fatigue ultra-high molecular weight polyethylene rope and a preparation method thereof. Under the combined action of the bauxite, the wear-resistant powder, the lubricant and the one-dimensional filling material, the fiber precursors forming the high-wear-resistance anti-fatigue ultra-high molecular weight polyethylene rope are not prone to deformation, the wear-resistant effect is good, and therefore the rope is suitable for being used as a mooring rope, and the rope is suitable for being used as a mooring rope. And friction generated when the cable is in contact with objects such as a ship side and a bollard can be fully borne, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ropes and cables, and more specifically, to a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope and cable and a preparation method thereof. Background Art

[0002] Marine engineering refers to engineering projects that are aimed at developing, utilizing, protecting and restoring marine resources, and the main part of the project is located on the seaward side of the coastline. Marine engineering ropes and cables refer to ropes and cables used in resource development and equipment and facility construction, and are usually used for mooring, anchoring, towing, lifting, etc. In recent years, with the gradual development of deep-sea resources, the requirements for ropes and cables in marine engineering are also gradually increasing.

[0003] Traditional marine engineering cables are generally steel wire ropes, but due to their heavy weight and lack of seawater corrosion resistance, they are being replaced by synthetic fiber ropes. Among the currently known synthetic fiber ropes, ropes made of ultra-high molecular weight polyethylene (UHMWPE) have the characteristics of ultra-high breaking strength, thin diameter, light weight, low elongation, high safety and high fatigue strength, so in theory they are more suitable for use in large ships, offshore drilling platforms, large fishery trawls, seawater cage farming and other occasions.

[0004] With regard to the above-mentioned related technologies, the inventors believe that although ropes made of ultra-high molecular weight polyethylene have the advantage of good corrosion resistance, when such ropes are used as mooring ropes, the friction between the ropes and objects such as the ship's side and mooring piles during use will cause the ropes to wear, thereby affecting the service life of the ropes. Summary of the invention

[0005] In the related art, ultra-high molecular weight polyethylene ropes are prone to wear when used as mooring ropes, which will affect the service life of the ropes. In order to improve this defect, the present application provides a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope and a preparation method thereof.

[0006] In the first aspect, the present application provides a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope, which adopts the following technical solution:

[0007] A highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope cable, the rope cable is woven from fiber filaments, the fiber filaments include the following components in parts by weight: 150-160 parts of base material, 6-8 parts of bauxite, 5-15 parts of anti-wear powder, 3-5 parts of lubricant, and 5-10 parts of one-dimensional filling material; the base material includes ultra-high molecular weight polyethylene resin, the anti-wear powder includes modified silicon carbide, the lubricant includes PTFE powder, and the modified silicon carbide is silicon carbide powder with silane segments grafted on the surface.

[0008] By adopting the above technical scheme, the present application optimizes the composition of the rope, and while selecting ultra-high molecular weight polyethylene resin as the base material, bauxite, anti-wear powder, lubricant, one-dimensional filling material are added to cooperate with the base material, and silicon carbide is modified using silane segments to obtain modified silicon carbide with good dispersion effect. Bauxite can promote the crystallization of ultra-high molecular weight polyethylene, and anti-wear powder represented by silicon carbide has a large hardness, so the synergistic effect of bauxite and anti-wear powder can improve the hardness of fiber precursors and reduce the deformation of the rope woven from the fiber precursors during the wear process. At the same time, the one-dimensional filling material, bauxite, and anti-wear powder can bear the external load together with the base material, so that the external force received by the rope during the wear process is dispersed, reducing the influence of the external load on the rope. Under the combined action of bauxite, anti-wear powder, lubricant and one-dimensional filling material, the fiber filaments constituting the rope are not easily deformed and have a better effect of resisting wear. Therefore, the rope of the present application is suitable for use as a mooring rope, can fully withstand the friction generated when contacting objects such as the ship's side and mooring piles, and has a long service life.

[0009] Preferably, the modified silicon carbide is prepared according to the following method:

[0010] Toluene, silicon carbide powder and silane coupling agent are mixed, heated and stirred under nitrogen protection, vacuum filtered while hot after the reaction is completed, the obtained powder is added into water for ultrasonic dispersion, then centrifugally washed, and dried to obtain modified silicon carbide; the silane coupling agent is γ-aminopropyltriethoxysilane.

[0011] By adopting the above technical solution, the present application preferably selects a method for preparing modified silicon carbide. The above method achieves uniform dispersion of silicon carbide through ultrasonic treatment, which helps to achieve sufficient modification of silicon carbide.

[0012] Preferably, in the method for preparing the modified silicon carbide, the heating temperature is 70-85°C.

[0013] By adopting the above technical solution, the present application optimizes the heating temperature of modified silicon carbide, which helps to fully realize the modification of silicon carbide.

[0014] Preferably, in the method for preparing the modified silicon carbide, the reaction time is 4-6 hours.

[0015] By adopting the above technical solution, the present application optimizes the reaction time, which helps to fully realize the modification of silicon carbide.

[0016] Preferably, in the method for preparing the modified silicon carbide, the amount of the silane coupling agent used is 2.5-3.5% by weight of the silicon carbide powder.

[0017] By adopting the above technical solution, the present application optimizes the dosage of the silane coupling agent, which helps to fully realize the modification of silicon carbide.

[0018] Preferably, the base material further comprises nylon-6, and the weight of the nylon-6 accounts for 8-12% of the total weight of the base material.

[0019] By adopting the above-mentioned technical scheme, the application has preferably nylon-6 as the second component of base material, and nylon-6 is easily entangled with the molecular weight of ultra-high molecular weight polyethylene resin, and the degree of entanglement increases along with the consumption growth of nylon-6.After nylon-6 and the molecular weight of ultra-high molecular weight polyethylene resin are entangled, it is possible to form a space network structure that intertwines with each other, and in addition nylon-6 can form a hydrogen bond with the amino group on the surface of modified silicon carbide, therefore synergistic effect is produced, the mechanical property of fiber precursor is improved, and the hardness of fiber precursor is improved.Along with the raising of fiber precursor hardness, the deformation and the wear and tear that external friction causes to fiber precursor also reduce thereupon, and therefore the rope cable formed by fiber precursor also possesses better wear resistance.

[0020] Preferably, the lubricant further comprises montmorillonite.

[0021] By adopting the above technical solution, montmorillonite has a lamellar structure, which can produce slip when subjected to external force, thereby playing a certain lubricating effect and reducing the wear of the fiber precursor. At the same time, the addition of montmorillonite can also promote the crystallization of nylon-6, help to increase the hardness of the fiber precursor, and enhance the resistance of the fiber precursor to wear. Through the synergistic effect of montmorillonite and nylon-6, the rope woven from the fiber precursor has good wear resistance and is suitable for long-term use as a mooring rope.

[0022] Preferably, the one-dimensional filling material comprises modified potassium hexatitanate nanowhiskers, and silane segments are grafted on the surface of the modified potassium hexatitanate nanowhiskers.

[0023] By adopting the above technical scheme, the modified potassium hexatitanate nanowhiskers can not only act as a one-dimensional filling material to bear external loads together with bauxite and wear-resistant powder, but also be entangled with the base material, thereby enhancing the network structure formed by the entanglement of molecular chains inside the base material, which helps to fully improve the wear resistance of the fiber precursor and the rope made of the fiber precursor.

[0024] Preferably, the one-dimensional filling material further comprises modified wollastonite fiber, and silane segments are grafted onto the surface of the modified wollastonite fiber.

[0025] By adopting the above technical scheme, the modified wollastonite fiber not only acts as a one-dimensional filling material to bear external loads together with bauxite and wear-resistant powder, but also has a strong bonding strength with the molecular chain of ultra-high molecular weight polyethylene resin, which helps to fully improve the wear resistance of the fiber precursor and the rope made of the fiber precursor.

[0026] In a second aspect, the present application provides a method for preparing a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope, which adopts the following technical solution.

[0027] A method for preparing a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope comprises the following steps:

[0028] (1) mixing a base material, bauxite, anti-wear powder, a lubricant and a one-dimensional filler material to obtain a mixture;

[0029] (2) adding the mixed material into the mold cavity for pre-pressing, then heating and kneading the mixed material in the mold cavity at 210-240° C., and after heat preservation treatment, sending the material into the spinning equipment, and obtaining fiber precursor after extrusion through the spinneret;

[0030] (3) The fiber raw filaments are braided to obtain a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope.

[0031] By adopting the above technical scheme, the present application first mixes the raw material components, then uses the obtained mixture to produce fiber precursors, and finally weaves the fiber precursors into highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene ropes. Under the joint action of bauxite, anti-wear powder, lubricant, and one-dimensional filling material, the fiber precursors constituting the ropes are not easy to deform and have a good effect of resisting wear. Therefore, the ropes of the present application are suitable for use as mooring ropes, can fully withstand the friction generated when contacting objects such as ship sides and mooring piles, and have a long service life.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The present application preferably selects bauxite, anti-wear powder, lubricant, and one-dimensional filling material as components of the fiber precursor. Under the joint action of bauxite, anti-wear powder, lubricant, and one-dimensional filling material, the fiber precursor constituting the cable is not easily deformed and has a better effect of resisting wear. Therefore, the cable of the present application is suitable for use as a mooring cable, can fully withstand the friction generated when in contact with objects such as the ship's side and mooring piles, and has a long service life.

[0034] 2. This application preferably uses nylon-6 as the second component of the base material. Nylon-6 is easy to entangle with the molecular weight of ultra-high molecular weight polyethylene resin, and after entanglement, it can form a mutually staggered spatial network structure. In addition, nylon-6 can form hydrogen bonds with the amino groups on the surface of modified silicon carbide, thereby synergistically improving the mechanical properties of the fiber precursor and increasing the hardness of the fiber precursor. As the hardness of the fiber precursor increases, the deformation and wear of the fiber precursor caused by external friction also decreases, so the rope made of the fiber precursor also has better wear resistance. DETAILED DESCRIPTION

[0035] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0036] Preparation example of modified silicon carbide

[0037] The following is an explanation using Preparation Example 1.

[0038] Preparation Example 1

[0039] In this preparation example, the average particle size of the silicon carbide powder is 0.897 μm.

[0040] In this preparation example, modified silicon carbide is prepared according to the following method:

[0041] Mix 350 mL of toluene, 50 g of silicon carbide powder and γ-aminopropyltriethoxysilane equivalent to 2% of the weight of the silicon carbide powder (referred to as the amount of silane in Table 3), heat and stir at 65°C (referred to as the reaction temperature in Table 1) under nitrogen protection, react for 3 hours (referred to as the reaction time in Table 2), and then perform vacuum filtration while hot. Add the obtained powder into water for ultrasonic dispersion, then perform centrifugal washing, and obtain modified silicon carbide after drying.

[0042] As shown in Table 1, the difference between Preparation Examples 1-5 is the different reaction temperatures.

[0043] Table 1 Reaction temperature

[0044]

[0045] As shown in Table 2, the difference between Preparation Examples 5-8 is the different reaction times.

[0046] Table 2 Reaction time

[0047]

[0048] As shown in Table 3, the difference between Preparation Examples 8-11 is that the amount of silane used is different.

[0049] Table 3 Reaction time

[0050]

[0051] Preparation example of modified potassium hexatitanate nanowhiskers

[0052] The following is an explanation using Preparation Example 12 as an example.

[0053] Preparation Example 12

[0054] The potassium hexatitanate nanowhiskers used in this preparation example have an average diameter of 15 nm and an average length of 2 μm.

[0055] In this preparation example, the modified potassium hexatitanate nanowhiskers were prepared according to the following method: 10 g of potassium hexatitanate nanowhiskers were added to 200 mL of heptane, and then 0.5 mL of octadecyltrichlorosilane was added, and the mixture was stirred at a rate of 600 r / min for 20 min and then filtered. The filter cake was washed with acetone and ethanol in turn, and then the filter cake was vacuum dried at 60° C. for 5 h to obtain the modified potassium hexatitanate nanowhiskers.

[0056] Preparation example of modified wollastonite fiber

[0057] The following is an explanation using Preparation Example 13 as an example.

[0058] Preparation Example 13

[0059] The wollastonite whiskers used in this preparation example had an average diameter of 0.14 μm and an average length of 2.8 μm.

[0060] In this preparation example, the modified wollastonite fiber was prepared according to the following method:

[0061] (1) In a vacuum air drying oven, the temperature is set to 100° C., and the wollastonite fiber is dried for 3 hours under this condition, and then used for later use; a mixed solution of γ-aminopropyltriethoxysilane and ethanol is prepared in a weight ratio of 1:1 to obtain a silane-modified solution, and then used for later use;

[0062] (2) Wollastonite fiber and silane modification liquid were mixed in a weight ratio of 10:1, stirred at a rate of 600 r / min for 10 min, and then placed in a vacuum air drying oven and dried at 75° C. to obtain modified wollastonite fiber.

[0063] Example

[0064] Examples 1-5

[0065] The following description is given by taking Example 1 as an example.

[0066] Example 1

[0067] This embodiment provides a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope. The diameter of the highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope is 24 mm. It is woven from fiber strands. The weaving method is set according to the 12-strand braided rope specified in "GB / T 30668-2014 Ultra-high molecular weight polyethylene fiber 8-strand, 12-strand braided rope and composite rope". The fiber strands include the following components: 150 kg base material, 6 kg bauxite, 5 kg anti-wear powder, 3 kg lubricant, and 5 kg one-dimensional filling material. The base material is ultra-high molecular weight polyethylene resin powder with a viscosity-average molecular weight of 1.8 million, the average particle size of bauxite is 1.2 μm, the anti-wear powder is the modified silicon carbide of Preparation Example 1, and the lubricant is PTFE micropowder with an average particle size of 0.8 μm; the one-dimensional filling material is potassium hexatitanate nanowhiskers, and the average diameter of potassium hexatitanate nanowhiskers is 15 nm and the average length is 2 μm.

[0068] This embodiment provides a method for preparing a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope, comprising the following steps:

[0069] (1) mixing a base material, bauxite, anti-wear powder, a lubricant and a one-dimensional filler material to obtain a mixture;

[0070] (2) adding the mixed material into the mold cavity for pre-pressing, then heating and kneading the mixed material in the mold cavity at 210° C. (referred to as the kneading temperature in Table 4), and after heat preservation treatment, sending the material into the spinning equipment, and obtaining fiber precursor after extrusion through the spinneret;

[0071] (3) The fiber raw filaments are braided in the form of 12 strands to obtain a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope.

[0072] As shown in Table 4, the differences between Examples 1-5 mainly lie in the different raw material ratios of the fiber precursors and the mixing temperatures.

[0073] Table 4 Raw material ratio and mixing temperature of fiber precursor

[0074] sample Example 1 Example 2 Example 3 Example 4 Example 5 Base material / kg 150 152 155 158 160 Bauxite / kg 6 6.5 7 7.5 8 Anti-wear powder / kg 5 8 10 12 15 Lubricant / kg 3 3.5 4 4.5 5 One-dimensional filling material / kg 5 6 8 9 10 Mixing temperature / ℃ 210 220 225 230 240

[0075] Example 5-15

[0076] As shown in Table 5, the difference between Examples 5-15 is that the modified silicon carbide is prepared with reference to different Examples.

[0077] Table 5

[0078] sample Preparation Example Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Example 7 Example 12 Preparation Example 8 Embodiment 13 Preparation Example 9 Embodiment 14 Preparation Example 10 Embodiment 15 Preparation Example 11

[0079] Example 16

[0080] The difference between this embodiment and Embodiment 15 is that the base material is composed of ultra-high molecular weight polyethylene resin and nylon-6, and the weight of nylon-6 accounts for 4% of the total weight of the base material (referred to as nylon proportion in Table 6).

[0081] As shown in Table 6, the difference between Examples 16-20 is that the proportion of nylon is different.

[0082] Table 6 Nylon proportion

[0083]

[0084] Embodiment 21

[0085] The difference between this embodiment and Embodiment 20 is that the lubricant further includes montmorillonite, and the weight of the montmorillonite accounts for 50% of the total weight of the lubricant.

[0086] Embodiment 22

[0087] The difference between this embodiment and Embodiment 21 is that the one-dimensional filling material is modified potassium hexatitanate nanowhiskers, and the modified potassium hexatitanate nanowhiskers are prepared according to the method of Preparation Example 12.

[0088] Embodiment 23

[0089] The difference between this embodiment and Example 22 is that the one-dimensional filling material also includes modified wollastonite fiber, the weight ratio of the modified wollastonite fiber to the modified potassium hexatitanate nanowhiskers is 1:2, and the modified wollastonite fiber is prepared according to the method of Preparation Example 13.

[0090] Comparative Example

[0091] Comparative Example 1

[0092] The difference between this comparative example and Example 1 is that the raw material for producing the fiber precursor only includes ultra-high molecular weight polyethylene resin powder with a viscosity average molecular weight of 1.8 million.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that the raw material for producing the fiber precursor does not include a lubricant.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 1 is that the raw material for producing the fiber precursor does not include a one-dimensional filling material.

[0097] Comparative Example 4

[0098] The difference between this comparative example and Example 1 is that the raw material for producing the fiber precursor does not include bauxite.

[0099] Comparative Example 5

[0100] The difference between this comparative example and Example 1 is that the raw material for producing the fiber precursor does not include anti-wear powder.

[0101] Performance testing methods

[0102] A 50 mm section of the rope of each embodiment and comparative example was cut out as a sample, and then each sample was tested using an Akron abrasion tester, with 300 turns, and the difference in weight of the sample before and after abrasion was recorded, and the ratio of the difference to the initial weight of the sample was calculated, and the ratio was recorded as the wear rate. Based on the wear rate of comparative example 1, the ratio between the wear rate of each embodiment and comparative example and the wear rate of comparative example 1 was calculated, and the ratio was recorded as the relative wear rate. The results are shown in Table 7.

[0103] Table 7 Relative wear rate

[0104]

[0105]

[0106] Combining Examples 1-5 and Comparative Example 1 and Table 7, it can be seen that the relative wear rates measured in Examples 1-5 are significantly lower than those in Comparative Example 1, indicating that under the joint action of bauxite, anti-wear powder, lubricant, and one-dimensional filling material, the fiber filaments constituting the cable are not easily deformed, and the wear resistance effect is better. Therefore, the cable of the present application is suitable for use as a mooring cable, can fully withstand the friction generated when in contact with objects such as the ship's side and mooring piles, and has a long service life.

[0107] Combining Example 1 and Comparative Examples 2-5 and Table 7, it can be seen that the relative wear rate measured in Example 1 is significantly lower than that in Comparative Examples 2-5, indicating that when bauxite, anti-wear powder, lubricant, and one-dimensional filling material are not compounded for use, the wear resistance of the cable cannot be fully improved due to the limited synergy between the components.

[0108] It can be seen from Examples 5-15 and Table 7 that setting the heating temperature at 70-85°C, the reaction time at 4-6h, and the amount of the silane coupling agent at 2.5-3.5% of the weight of the silicon carbide powder are all helpful to fully achieve the modification of the silicon carbide powder. By fully modifying the silicon carbide powder, the silicon carbide powder can be evenly dispersed in the fiber precursor, so that the synergistic effect of the anti-wear powder and other components can be fully exerted, which helps to fully improve the wear resistance of the rope.

[0109] It can be seen from Example 15, Examples 16-20 and Table 7 that the relative wear rates measured in Examples 16-20 are significantly lower than those in Example 15. This is because nylon-6 improves the mechanical properties of the fiber precursor and increases the hardness of the fiber precursor. As the hardness of the fiber precursor increases, the deformation and wear of the fiber precursor caused by external friction also decreases, so the ropes and cables woven from the fiber precursors also have better wear resistance. When the amount of nylon-6 accounts for 8-12% of the total weight of the base material, the wear resistance of the rope is better.

[0110] Combining Example 20, Example 21 and Table 7, it can be seen that the relative wear rate measured in Example 21 is lower than that in Example 20. This is because montmorillonite has a lamellar structure, which can produce slip when subjected to external force, thereby playing a certain lubricating effect and reducing the wear of the fiber precursor. In addition, montmorillonite can also promote the crystallization of nylon-6, thus helping to increase the hardness of the fiber precursor and enhancing the resistance of the fiber precursor to wear.

[0111] Combining Example 21, Example 22 and Table 7, it can be seen that the relative wear rate measured in Example 22 is lower than that in Example 21. This is because the modified potassium hexatitanate nanowhiskers, in addition to acting as a one-dimensional filling material to bear external loads together with bauxite and wear-resistant powder, can also be entangled with the base material, thereby enhancing the network structure formed by the entanglement of molecular chains inside the base material, thereby helping to fully improve the wear resistance of the fiber precursor and the rope made of the fiber precursor.

[0112] It can be seen from Example 22, Example 23 and Table 7 that the relative wear rate measured in Example 23 is lower than that in Example 22. This is because the modified wollastonite fiber, in addition to being a one-dimensional filling material that bears external loads together with bauxite and wear-resistant powder, also has a strong bonding strength with the molecular chain of the ultra-high molecular weight polyethylene resin, thereby helping to fully improve the wear resistance of the fiber precursor and the rope made of the fiber precursor.

[0113] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope, characterized in that: The rope is woven from fiber filaments, which include the following components in parts by weight: 150-160 parts of base material, 6-8 parts of bauxite, 5-15 parts of anti-wear powder, 3-5 parts of lubricant, and 5-10 parts of one-dimensional filling material; the base material includes ultra-high molecular weight polyethylene resin, the anti-wear powder includes modified silicon carbide, the lubricant includes PTFE powder, and the modified silicon carbide is silicon carbide powder with silane segments grafted on the surface.

2. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 1, characterized in that: The modified silicon carbide is prepared according to the following method: Toluene, silicon carbide powder and silane coupling agent are mixed, heated and stirred under nitrogen protection, vacuum filtered while hot after the reaction is completed, the obtained powder is added into water for ultrasonic dispersion, then centrifugally washed, and dried to obtain modified silicon carbide; the silane coupling agent is γ-aminopropyltriethoxysilane.

3. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 2, characterized in that: In the method for preparing the modified silicon carbide, the heating temperature is 70-85°C.

4. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 2, characterized in that: In the method for preparing the modified silicon carbide, the reaction time is 4-6 hours.

5. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 2, characterized in that: In the method for preparing the modified silicon carbide, the amount of the silane coupling agent used is 2.5-3.5% of the weight of the silicon carbide powder.

6. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 5, characterized in that: The base material also includes nylon-6, and the weight of the nylon-6 accounts for 8-12% of the total weight of the base material.

7. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 6, characterized in that: The lubricant also includes montmorillonite.

8. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 1, characterized in that: The one-dimensional filling material comprises modified potassium hexatitanate nano whiskers, and the surface of the modified potassium hexatitanate nano whiskers is grafted with silane segments.

9. The highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to claim 8, characterized in that: The one-dimensional filling material also includes modified wollastonite fiber, and silane segments are grafted on the surface of the modified wollastonite fiber.

10. The method for preparing the highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing a base material, bauxite, anti-wear powder, a lubricant and a one-dimensional filler material to obtain a mixture; (2) adding the mixed material into the mold cavity for pre-pressing, then heating and kneading the mixed material in the mold cavity at 210-240° C., and after heat preservation treatment, sending the material into the spinning equipment, and obtaining fiber precursor after extrusion through the spinneret; (3) The fiber raw filaments are braided to obtain a highly wear-resistant and fatigue-resistant ultra-high molecular weight polyethylene rope.